DESAIN MEDIA PEMBELAJARAN FISIKA MENGGUNAKAN SOFTWARE PREZI BERBASIS SCIENTIFIC MATERI TATA SURYA KELAS VIII - Tias, Dini Maryuning; Astalini, Astalini; Pathoni, Haerul (EduFisika: Jurnal Pendidikan Fisika, 2019)
The research aims to develop physics learning media using scientific-based prezi software for VIII SMP grade solar system material. Research includes research and development with the ADDIE model. The subjects of this research trial were media experts and class VIII A students at SMP Negeri 11 Muaro Jambi. The research instruments used were preliminary study questionnaires, material and media validation questionnaires and student perception questionnaires. The data analysis technique of students' perceptions was carried out using descriptive statistics. Product specifications namely prezi software using exe format. The results of the validation of the expert stated that the design used was in accordance with the subject matter and learning objectives so that it was declared valid. The perception test results of 68.12 students in the excellent category and reliability 0.8281 in the very high category. Based on the results obtained that the scientific media prezi based on solar system material is suitable for use as teaching material.